A plate diffusion method for detecting fluoroquinolone residues in raw cow's milk - Pavlína NAVRÁTILOVÁ; Jana VYHNÁLKOVÁ; Lenka VORLOVÁ; Jaroslava JEŘÁBKOVÁ (Czech Journal of Food Sciences, 2014)
The plate diffusion method is a reference method in the Czech Republic for determination of residues of antimicrobial agents in raw materials and foodstuffs of animal origin. A new method using the E. coli strain ATCC 11303 for the detection of fluoroquinolones was introduced in 2008. The aim of this study was to determine the detection capability (CCβ) of this modified method using this E. coli strain for selected fluoroquinolones registered in the Czech Republic for treating diseases in cattle - danofloxacin, marbofloxacin, ciprofloxacin, enrofloxacin, and flumequine. When comparing the maximum residue limits for individual fluoroquinolones and the CCβ values determined, we can state that the method displays very good sensitivity to ciprofloxacin and enrofloxacin (20 and 40 µg/l), marbofloxacin (70 µg/l), and danofloxacin (30 µg/l). The CCβ of the method for flumequine was not found in concentrations ≤ MRL. The method did not display sensitivity to flumequine even in a concentration equal to twelve times the MRL.